(untitled) (Latakia University Journal -Basic Sciences Series, 2016)
ركّز هذا البحث على دراسة إعادة تجديد الزيوت المعدنيّة المستهلكة باستخدام االتقانة الإشعاعية كطريقة فعّالة ونظيفة، يمكن من خلالها الوصول إلى منتج يحققّ المواصفات اللازمة لاستخدامه كمزلق في المجالات المختلفة، حيث تمّ في هذه الدراسة معالجة الزيوت المعدنيّة المستهلكة وفق ثلاث طرائق: المعالجة الفيزيائية, الإشعاعية, والمعالجة المزدوجة الإشعاعية الكيميائية باستخدام أشعّة غاما والمونوميرات. تبيّن النتائج أنّ المعالجة المزدوجة الإشعاعية الكيميائية باستخدام أشعة غاما والمونوميرات ، هي أفضل طريقة بين طرائق المعالجة الثلاث، للحصول على مؤشرات جيّدة للزيوت المعدنية المستهلكة، حيث أظهرت النتائج التجريبية تحسّناً ملحوظاً في قيم مؤشرات (اللزوجة، درجة الانصباب، درجة الوميض، رقم الحموضة، اختبارات تآكل صفيحة النحاس)، للزيوت المعدنية المختبرة. كما أنّ قيم المؤشرات السابقة تتحسن بازدياد نسبة الإضافة من المونومير وقيمة الجرعة الإشعاعية. This research concentrated on regeneration of mineral used oils by using radiation technology as clean and effective method to have a product with specifications which are necessary to use it as good lubricant in different fields. In this study the mineral oils were treated in three methods: Physical, Radiation and Paired chemical and radiation treatment by using gamma rays and monomers. This study show that the Paired chemical and radiation treatment by using gamma rays and monomers is the better method between the three methods to have good parameters of mineral used oils. The experimental methods show observed improvement in values of the following parameters (viscosity, Poure point, flash point, number acid, detection of copper corrosion from petroleum Products by copper strip tarnish test). The values of last parameters increased by increasing the radiation dose and proportion of monomer addition